An Islamic Perspective of Superstitious Practices Related to Will (Al-Waṣiyyah) Among Yoruba of Southwest Nigeria - Badrudeen , Musa Adebayo (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Superstition, as an unscientific and irrational belief, is a long and common practice across the globe and almost in every aspect of human endeavor be it economic, moral, social, psychological and religious. Will, is one of the means of acquiring wealth and taking over the ownership of a portion of an estate after the demise of the real owner. However there are some superstitions that are related to it and are so believed and practiced by people around the world in general and Yoruba people of Nigeria in particular. Therefore, this paper aims at uncovering the degree of involvement of the Yoruba Muslims of southwest Nigeria in the superstitious practices related to will. The paper also discusses the Islamic perspective of the practices. Descriptive and analytical research methods were used in this work. The research findings reveal that ignorance of some Yoruba Muslims of the Islamic systems of Will and Inheritance and their strict adherence to the Yoruba culture are the salient factors influencing them to the involvement in the superstitious practices related to Will. The paper, therefore, concludes by encouraging creation and promotion of more awareness on the significance and relevance of Islamic system of Will not only to the individual Muslim but also to the entire Yoruba people.